Genetic variations in regions of bovine and bovine-like enteroviral 5'UTR from cattle, Indian bison and goat feces. Issue 1 (December 2016) - Kosoltanapiwat, Nathamon; Yindee, Marnoch; Chavez, Irwin; Leaungwutiwong, Pornsawan; Adisakwattana, Poom; Singhasivanon, Pratap; Thawornkuno, Charin; Thippornchai, Narin; Rungruengkitkun, Amporn; Soontorn, Juthamas; Pearsiriwuttipong, Sasipan
Abstract Background Bovine enteroviruses (BEV) are members of the genusEnterovirus in the familyPicornaviridae . They are predominantly isolated from cattle feces, but also are detected in feces of other animals, including goats and deer. These viruses are found in apparently healthy animals, as well as in animals with clinical signs and several studies reported recently suggest a potential role of BEV in causing disease in animals. In this study, we surveyed the presence of BEV in domestic and wild animals in Thailand, and assessed their genetic variability. Methods Viral RNA was extracted from fecal samples of cattle, domestic goats, Indian bison (gaurs), and deer. The 5' untranslated region (5'UTR) was amplified by nested reverse transcription-polymerase chain reaction (RT-PCR) with primers specific to BEV 5'UTR. PCR products were sequenced and analyzed phylogenetically using the neighbor-joining algorithm to observe genetic variations in regions of the bovine and bovine-like enteroviral 5'UTR found in this study. Results BEV and BEV-like sequences were detected in the fecal samples of cattle (40/60, 67 %), gaurs (3/30, 10 %), and goats (11/46, 24 %). Phylogenetic analyses of the partial 5'UTR sequences indicated that different BEV variants (both EV-E and EV-F species) co-circulated in the domestic cattle, whereas the sequences from gaurs and goats clustered according to the animal species, suggesting that these viruses are host species-specific. Conclusions Varieties of BEV and BEV-like 5'UTR sequences were detected in fecal samples from both domestic and wild animals. To our knowledge, this is the first report of the genetic variability of BEV in Thailand.